2012
DOI: 10.4103/0970-4388.105010
|View full text |Cite
|
Sign up to set email alerts
|

Parental acceptance of pediatric behavior management techniques: A comparative study

Abstract: Factors such as having a disabled child, low income, and less education influenced parental acceptability. HOM should be used with great caution and clinicians should approach the issue of informed consent on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 0 publications
5
17
0
6
Order By: Relevance
“…These findings were consistent with another study which found physical restraint technique unacceptable by parents, however, the parents accepted GA in emergency dental situations [16]. The acceptance of general anesthesia and sedation has shown an increase in the present study when compared other studies conducted on Indian populations [5,6]. In the present study, parents received explanations on the various behavior management techniques intended to be used by the dentists involved in the research, what may be the reason why parents showed general acceptability toward various behavior management techniques.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings were consistent with another study which found physical restraint technique unacceptable by parents, however, the parents accepted GA in emergency dental situations [16]. The acceptance of general anesthesia and sedation has shown an increase in the present study when compared other studies conducted on Indian populations [5,6]. In the present study, parents received explanations on the various behavior management techniques intended to be used by the dentists involved in the research, what may be the reason why parents showed general acceptability toward various behavior management techniques.…”
Section: Discussionsupporting
confidence: 83%
“…Parental attitudes are constantly changing as society evolves so it is important to regularly reassess their beliefs and update our understanding of their attitudes toward behavior management techniques [4]. There have been many studies assessing the parental acceptance and rating of various behaviour management techniques in children; however, few studies were conducted on Indian parents [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in a study indicated that parents with lower educational level, low income and with disabled children showed higher acceptability in relation to BG methods [13].…”
Section: Discussionmentioning
confidence: 94%
“…10 The BMTs should be learned and developed by all staff in the pediatric dental clinic, starting with the receptionist, who welcomes the parents and their child and ending with the pediatric dentist, who will perform the treatment. 6,7 Parental presence/absence is one of the nonpharmacological BMTs. In this technique, the parental presence is used as a factor to manage the child's negative behavior.…”
Section: 5005/jp-journals-10024-2243mentioning
confidence: 99%
“…Without such a skill, dentists would not be able to deliver appropriate and safe treatment. [3][4][5][6][7] In 1895, McElroy wrote: "Although the operative dentistry may be perfect, the appointment is a failure if the child departs in tears". 8 This was considered the first base mentioned in the pediatric dental literature to measure success or failure of a child's dental visit.…”
Section: Introductionmentioning
confidence: 99%